2002
DOI: 10.1111/1475-6811.09406
|View full text |Cite
|
Sign up to set email alerts
|

Intimacy and the magnitude and experience of episodic relational uncertainty within romantic relationships

Abstract: This paper seeks to clarify the association between the intimacy and the magnitude of relational uncertainty generated by specific events within romantic relationships. More specifically, we suggest that episodic relational uncertainty peaks at moderate levels of intimacy. We conducted a cross-sectional study in which 328 romantic relationship participants reported their reactions to a hypothetical relational uncertainty increasing event. Although the effect size was small, findings documented a curvilinear as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
169
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(183 citation statements)
references
References 40 publications
10
169
4
Order By: Relevance
“…Namely, general partner uncertainty first occurs within the jealous target and precedes relational uncertainty as an exogenous variable. Similar to Knobloch and Solomon's (2002) findings, the association between partner and relational uncertainty spans relational contexts and situations. These overall findings inform the process of uncertainty arousal and the associations between partner and relational uncertainty introduced by Knobloch and Solomon (1999).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Namely, general partner uncertainty first occurs within the jealous target and precedes relational uncertainty as an exogenous variable. Similar to Knobloch and Solomon's (2002) findings, the association between partner and relational uncertainty spans relational contexts and situations. These overall findings inform the process of uncertainty arousal and the associations between partner and relational uncertainty introduced by Knobloch and Solomon (1999).…”
Section: Discussionsupporting
confidence: 71%
“…Hypothetical scenarios were used to avoid retrospective recall biases, measure participants' immediate and direct response to the event of interest, and provide control over the specific situations that participants consider (Knobloch & Solomon, 2002). Further, recent research (Knobloch, 2005) found that associations between uncertainty, emotions (including jealousy), and appraisals did not vary according to whether the data were retrospective recall or hypothetical events.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of dyadic gender composition, Gudykunst, Nishida, and Schmidt (1989) and Gudykunst, Sodetani, and Sonoda (1987) did not observe significant differences for communicative aspects of uncertainty reduction in United States culture. In contrast, Knobloch and Solomon (2002) found that female dating partners experienced greater partner and relational uncertainty than did males. Thus, although H2's finding is not consistent with sibling gender composition research, it is in line with most studies that have investigated uncertainty and gender.…”
Section: Sibling Gender Compositionmentioning
confidence: 74%
“…A lingering question is whether individuals may be dissatisfied when partners are unsure. People experiencing relational uncertainty act in ways that may be aggravating: They avoid talking about sensitive issues (Knobloch & Carpenter-Theune, 2004;Knobloch & Solomon, 2002b), communicate indirectly about problems (Theiss & Solomon, 2006a, 2006b, and have difficulty producing and processing messages competently (Knobloch, 2006;Knobloch & Solomon, 2005). If partners grappling with relational uncertainty engage in such frustrating behaviors, actors may experience relationship distress.…”
Section: Relational Uncertainty and Relationship Qualitymentioning
confidence: 99%